2015
DOI: 10.1007/s00774-015-0659-1
|View full text |Cite
|
Sign up to set email alerts
|

The effects of α-zearalanol on the proliferation of bone-marrow-derived mesenchymal stem cells and their differentiation into osteoblasts

Abstract: The aim of this study was to explore the effects of α-zearalanol (α-ZAL) on the proliferation of mouse bone-marrow-derived mesenchymal stem cells (BMSCs) and their differentiation into osteoblasts. Six- to eight-week-old BALB/C mice were used either as recipients or as bone marrow donors. BMSCs were isolated and collected using a differential adhesion method, with use of 10 % fetal bovine serum and Iscove's modified Dulbecco's medium. After the third generation, the BMSCs were randomly placed into the followin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…ZEA, at a low concentration, enhanced cell proliferation of a colon carcinoma cell line [12]. It has also been suggested that α-ZAL can increase the proliferation of bone marrow stromal cells and of granulosa cells [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…ZEA, at a low concentration, enhanced cell proliferation of a colon carcinoma cell line [12]. It has also been suggested that α-ZAL can increase the proliferation of bone marrow stromal cells and of granulosa cells [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…What’s more, several studies have indicated that the derivatives of ZEA can also stimulate cell growth. α-zearalanol (α-ZAL), one of the derivatives of ZEA, could effectively stimulate the proliferation of BMS cells, induce differentiation into osteoblasts and suppress osteoclastogenesis formation [ 12 ]. α-Zearalenol (α-ZEL), the another one derivative of ZEA, showed a strong effect of stimulating on granulosa cells, even when treated with fumonisin B1 (FB1) which could inhibit the growth of granulosa cells [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we found that after the addition of PL, the expression levels of OPG, OCN, OPN, ALP protein were increased, but the expression level of RANKL protein did not change, the ratio of OPG/RANKL was increased. Researchers isolated various types of cells from bone delayed healing tissues, such as long fusiform or short fusiform, which were similar to nonunion cells and could differentiate to nonunion cells ( 19 ). But female nonunion cells were affected by estrogen and progesterone, influenced the reliability of experimental results.…”
Section: Discussionmentioning
confidence: 99%